Neottia motuoensis (Neottieae, Orchidaceae), a new species from Xizang, China - Wen, Haixia; Ye, Chao; Lin, Dongliang; Li, Jianwu; Song, Xiqiang; Jin, Xiaohua (Phytotaxa, 2024)
Neottia motuoensis (Neottieae, Orchidaceae), a new species from Motuo, Xizang Autonomous Region, China, was described and illustrated. Neottia motuoensis is similar to N. yunnanensis, but differs from it by having lip with side lobes at the base, disk with a pair of fleshy calli between lateral lobes, lobelets of the labellum short and rounded.